Evaluation of Vitamin D3 and D2 Stability in Fortified Flat Bread Samples During Dough Fermentation, Baking and Storage - Mehrnaz Tabibian; Mohammadali Torbati; Mohammad Reza Afshar Mogaddam; Maryam Mirlohi; Malihe Sadeghi; Javad Mohtadinia (Tabriz University of Medical Sciences, 2017)
Purpose: Vitamin D, a fat-soluble secosteroid, has a significant role in bone metabolism and helps calcium absorption in the body. Since vitamin D concentration is altered in fortified foods and dietary supplements, the actual amount of vitamin D may differ from the label value. Methods: In this study, the concentrations of vitamin D2 and D3 of fortified bread sample were analytically determined. For this purpose, dough or homogenized bread sample was saponified using potassium hydroxide solution (30%, w/v) at 80°C, and the saponified analytes were extracted into n-heptane followed by liquid-liquid extraction. Then n-heptane fraction was evaporated to dryness and the sample was reconstituted in methanol. The effect of different parameters was evaluated by one variable at one-time strategy. Results: The analytes concentrations were evaluated in dough fermentation, baking and storage steps. The effect of temperature in dough fermentation and baking was evaluated at the range of 5-30 and 200-250°C, respectively. Also, the fermentation time was studied in the range of 0-120 min. The analytes concentrations were followed for 1 to 5 days after baking. The results indicated that dough fermentation temperature has no significant effect on the concentration of the analytes. On the other hand, when the dough fermentation time and baking temperature are increased, the analytes concentrations are decreased. Also, the storage duration of the spiked bread samples decreased the analytes concentrations after one day. Conclusion: Based on the obtained results, baking the dough at high temperatures lead to decrease in vitamin levels.